Pelatihan: Data Analytics for Business Decision Making Using Stata, Implikasi Riset Akuntansi di Prodi Akuntansi UIN Syarif Hidayatullah Jakarta - Tambun, Sihar; Sitorus, Riris Rotua (Jurnal Pemberdayaan Nusantara, 2025)
Research data processing and analysis skills are no longer merely required competencies, but rather an integral requirement for prospective accounting graduates. This need underlies the Stata software training program for accounting students at UIN Syarif Hidayatullah Jakarta. The training aimed to educate students on how to process accounting research data using panel data using Stata software. The training covered data input, data testing techniques for research needs, and data interpretation. The training resulted in participants being able to independently process panel data using Stata software and interpret accounting research results. The training was evaluated on participants who had never studied Stata software before. The results showed a significant increase in data processing skills, from those who had no skills at all to those who could independently process data. Although the majority of participants already understood the software, they needed to practice these skills continuously to become more accustomed to and independently process panel data-based accounting research data